The Development of Legal Frameworks for Recyclable Waste Management by Local Government Organizations - Laehmuso, Rusleena; Keawphang, Sattra (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research article aim to study the issues of participation by producers and the public in the management of recyclable waste, by comparing foreign laws and proposing guidelines for the development of Thai legislation. The research is based on a qualitative research, by conducting document research, analyzing provisions of Thai law, foreign laws, and relevant academic documents. Research findings show that Thai law lacks provisions that clearly define the duties of producers and the public in separating and managing recyclable waste, and there are no economic measures to create incentives. As a result, the burden of waste management mainly falls on local government organizations, leading to less effective recycling management. In contrast, the laws of the Federal Republic of Germany, the Republic of Korea (South Korea), and Japan clearly define the responsibilities of producers and the public and use economic measures to promote tangible participation. Therefore, Thailand should develop its laws by specifying duties for separating recyclable waste, defining the responsibilities of producers, and implementing economic measures to sustainably improve the efficiency of recyclable waste management by local government organizations.